TINJAUAN YURIDIS NORMATIF TERHADAP PERALIHAN HAK ATAS TANAH KARENA PEWARISAN MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH - Anggoro, Denny Widi; Savitri, Miya Savitri (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
The soil has a close relationship with humans for land has economic value for human life and can generate resources for the people. This is regulated in Article 33 paragraph (3) of the Act of 1945 which states: